Pengaruh Kepemilikan Institusional, Kepemilikan Managerial Dan Good Corporate Governance Terhadap Praktik Manajemen Laba Pada Perusahaan Perbankan 2017-2021 - Ratna Widyanti Wahyuningsih (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
Profit is an indicator of operational performance so that business success and failure can be seen from the profits earned by the company. To attract the interest of investors and other related parties, earnings management violations were carried out in the financial statements so that the company appeared to be making profits that did not match reality. To prevent this, it is necessary to analyze the factors that influence earnings management. This study aims to analyze the effect of Institutional Ownership, Managerial Ownership and Good Corporate Governance on Profit Management in Banking Companies in 2017-2021. This type of research is explanatory research with secondary data sources from the official website of the Indonesian Stock Exchange. The research population was 41 banking companies listed on the Indonesia Stock Exchange in 2017-2021 with a sample size of 26 companies according to the criteria set. Analysis of research data through the PLS program. The research results prove that Institutional Ownership and Managerial Ownership have a significant negative effect on earnings management, Except for Good Corporate Governance. So to reduce earnings management, companies need to pay attention to Institutional Ownership, Managerial Ownership and Good Corporate Governance in research.